1997
DOI: 10.1002/(sici)1097-4644(19970601)65:3<340::aid-jcb4>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen responsiveness of renal calbindin-D28k gene expression in rat kidney

Abstract: In women, calcium excretion in the urine rises after menopause and falls with estrogen replacement therapy. The amount of calcium lost in the urine following estrogen therapy is less than should occur based on changes in serum calcium and the amount of calcium filtered by the kidney. This suggests there may be a direct effect of estrogen therapy to increase renal calcium reabsorption. Calbindin D28k is a putative calcium ferry protein located in the distal renal tubules which has been shown to increase transce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Among postmenopausal women, however, estrogen replacement therapy resulted in unchanged or increased renal 1␣-OHase activity (30,34 (20,29,36,37). In contrast, some studies suggested a direct effect of 17␤-E 2 on Ca 2ϩ reabsorption, independent of vitamin D (3,28).…”
Section: Discussionsupporting
confidence: 87%
“…Among postmenopausal women, however, estrogen replacement therapy resulted in unchanged or increased renal 1␣-OHase activity (30,34 (20,29,36,37). In contrast, some studies suggested a direct effect of 17␤-E 2 on Ca 2ϩ reabsorption, independent of vitamin D (3,28).…”
Section: Discussionsupporting
confidence: 87%
“…In keeping with these findings, another study in rats found that estradiol's ability to increase intestinal calcium absorption was independent of 1,25(OH) 2 D 3 [201]. A study by Criddle et al [202] suggests the decrease in renal calcium excretion associated with estrogen replacement is independent of 1,25(OH) 2 D 3 and may be dependent on increased expression of calbindin D28k protein, located in the distal renal tubule. Furthermore, Liel et al [203] found that the administration of estrogen to ovariectomized rats was found to increase intestinal calcium absorption by increasing the activity of duodenal vitamin D receptors (VDRs), rather than increasing levels of 1,25(OH) 2 D 3 .…”
Section: Estradiolsupporting
confidence: 76%
“…Only 18% of this increase in basal output can be accounted for by the increase in the serum (ultrafiltrable) calcium concentration; the rest is associated with the reduced tubular reabsorption of calcium that we have previously reported [14,15] and that is compatible with the in vitro effect of estrogen on calcium transport in the kidney [28]. This fall in TmCa is not due to a fall in serum PTH (which tends to rise) and suggests the loss of a direct effect of estrogen on renal tubular calcium transport, presumably mediated by the estrogen receptors in the kidney [29].…”
Section: Discussionmentioning
confidence: 99%